Economic evaluation of pharmacotherapeutic follow-up in type 2 diabetic mellitus patients in community pharmacies - Correr, Cassyano Januario (2015)
Objective: Assess economics results of Pharmacotherapeutic Follow-up (PF) in patients with diabetes mellitus type 2 in community pharmacies from additional Health system. Methods: In a prospective clinic study, 161 patients were divided into two groups, of which only one group received PF for 12 months. From the results, we calculated data of effectiveness and costs. The primary endpoint was the economic evaluation PF by using an indicator of effectiveness (changes in glycated hemoglobin), which was related to the costs of pharmaceutical care. Secondary endpoints were values of blood pressure, waist circumference and body mass index of patients, also related to costs of pharmaceutical care. Results: A real reduction of 1.3% of HbA1 was observed in the PF group, in comparison to control group. The annual cost of the reduction in 1% in HbA1 values in the PF group patients was $45.15. This feature to improve the control of type 2 diabetic patients can be implemented with annual investments of about $225.76 per patient, using PF and monitoring of blood glucose test. Conclusions: It is possible to reduce the HbA1 values to desired levels by using PF. This can be considered an additional resource for the attainment of metabolic control, resulting in this study a cost of $3762 per patient, per year, to reduce 1% in the HbA1 values. Arq Bras Endocrinol Metab. 2009;53(7): 825-33.